Analysis of balanced three-phase induction motor performance under unbalanced supply using simulation and experimental results - (:unkn) unknown (My University, 2011)
Induction motors are known to affect the electrical power system in terms of harmonics. Induction motors fed by unbalanced power systems produce additional current harmonics. These harmonics cause additional power losses in the machine. The method of symmetrical components is often used in this kind of unbalanced operation analysis. In this study, the performance of a three phase induction motor supplied by unbalanced power system due to the various causes has been examined using both experimental method and Matlab/Simulink model.